2019
DOI: 10.1097/pec.0000000000001656
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Statement on Urgent Care Centers and Retail Clinics in Acute Care of Children

Abstract: This article provides recommendations for pediatric readiness, scope of services, competencies, staffing, emergency preparedness, and transfer of care coordination for urgent care centers (UCCs) and retail clinics that provide pediatric care. It also provides general recommendations for the use of telemedicine in these establishments. With continuing increases in wait times and overcrowding in the nation's emergency departments and the mounting challenges in obtaining timely access to primary care providers, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…This equipment and these medications reduce morbidity and mortality in cases of significant head/neck injuries, hemorrhagic shock associated with trauma, and persistent blood loss, respectively. Although both the American Academy of Pediatrics and the American College of Emergency Physicians have suggested that urgent cares have certain equipment and medications available for both medical and traumatic emergencies, there are no national guidelines specific to PUCs 1,2 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This equipment and these medications reduce morbidity and mortality in cases of significant head/neck injuries, hemorrhagic shock associated with trauma, and persistent blood loss, respectively. Although both the American Academy of Pediatrics and the American College of Emergency Physicians have suggested that urgent cares have certain equipment and medications available for both medical and traumatic emergencies, there are no national guidelines specific to PUCs 1,2 …”
Section: Discussionmentioning
confidence: 99%
“…Although both the American Academy of Pediatrics and the American College of Emergency Physicians have suggested that urgent cares have certain equipment and medications available for both medical and traumatic emergencies, there are no national guidelines specific to PUCs. 1,2 Similarly, there are a lack of PUC-specific evidence-based guidelines for the management of trauma. Pediatric urgent cares often rely on guidelines meant to apply to the ED setting, such as those from the Pediatric Emergency Care Applied Research Network.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Currently, UC outnumbers emergency departments (EDs) and the industry is expected to expand further. [2][3][4] They are designed to provide acute care for minor illness and injury and neither UC or physician-based office practices (henceforth termed ambulatory care practices [ACPs]) are equipped to treat more emergent major illness or injury. 2 There are limited data on the number of emergencies at such facilities; quite dated work suggested a relatively high rate of out-patient visits requiring urgent treatment, on the order of one child per week per clinician.…”
Section: Introductionmentioning
confidence: 99%